2013
DOI: 10.1016/j.applanim.2012.10.010
|View full text |Cite
|
Sign up to set email alerts
|

The effects of predictability in daily husbandry routines on captive rhesus macaques (Macaca mulatta)

Abstract: Rhesus macaques (Macaca mulatta) housed indoors experience many routine husbandry activities on a daily basis. The anticipation of these events can lead to stress, regardless of whether the events themselves are positive or aversive in nature. The specific goal of this study was to identify whether increasing the predictability of husbandry events could decrease stress and anxiety in captive rhesus macaques. This study was conducted on 39 single-housed subjects in four indoor rooms at the Oregon National Prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 38 publications
0
42
2
1
Order By: Relevance
“…Conversely, other studies have found that making feeding sessions predictable is an eff ective way to decrease the stress associated with both waiting for and experiencing these events (Krishnamurthy, 1994;Ulyan et al, 2006;Gottlieb et al, 2013). These fi ndings are contrary to the common idea that animals fed on a predictable schedule undergo a high level of anticipation and stress (Bassett and Buchanan-Smith, 2007).…”
Section: Introductioncontrasting
confidence: 55%
See 2 more Smart Citations
“…Conversely, other studies have found that making feeding sessions predictable is an eff ective way to decrease the stress associated with both waiting for and experiencing these events (Krishnamurthy, 1994;Ulyan et al, 2006;Gottlieb et al, 2013). These fi ndings are contrary to the common idea that animals fed on a predictable schedule undergo a high level of anticipation and stress (Bassett and Buchanan-Smith, 2007).…”
Section: Introductioncontrasting
confidence: 55%
“…These fi ndings are contrary to the common idea that animals fed on a predictable schedule undergo a high level of anticipation and stress (Bassett and Buchanan-Smith, 2007). Gottlieb et al (2013) suggested that a predictable schedule removes the "unknown" of the session, and even though it builds anticipation, it is less stressful than not knowing when food will be delivered. Moreover, when animals are fed on a temporal unpredictable schedule, they activate responses that can be adaptive when the individuals have a degree of control over the environment, for example by increasing the amount of exploration (Reneerkens et al, 2002).…”
Section: Introductioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Full body repetitive behaviors, known as motor stereotypic behaviors (MSBs), are the most commonly seen abnormal behavior in rhesus macaques (Lutz et al, 2003); in a survey of three National Primate Research Centers, 18-49% of singly housed rhesus monkeys were reported as displaying some form of MSB, such as repetitive pacing, bouncing, swaying, rocking, or somersaulting (Lutz et al, 2011). Because they are often linked to frustration, lack of stimulation, lack of environmental control, and/or unavoidable stress (Mason, 1991; Mason and Latham, 2004; Mench and Mason, 1997), MSBs are frequently used as a behavioral metric to help evaluate captive primate well-being (e.g., Bayne et al, 1991; Gottlieb et al, 2013b; Novak et al, 1998). Common remediation strategies include foraging enrichment and socialization.…”
Section: Introductionmentioning
confidence: 99%
“…When these predictions are no longer accurate, due to shifts in food peaks or changes in weather patterns, the behaviours that were adaptive during many species' evolutionary history can become a problem [33,48]. In addition, animals' inability to predict events increases their stress response, and as such lowers their overall health [49]. Since predictability of environmental events is limited not only to the frequency and regularity of the events, but also to the cognitive abilities and experience of the individual, prediction affects whether and how an individual might respond, and as such can be considered a relevant attribute of the process of change.…”
Section: Predictionmentioning
confidence: 99%